FORMULASI DAN UJI AKTIVITAS ANTIBAKTERI SEDIAAN ACNE PATCH EKSTRAK ETANOL DAUN CENGKIH (Syzygium aromaticum) TERHADAP BAKTERI Propionibacterium acnes - Nurfadilah, Ratna; Rizkuloh, Lina Rahmawati; Nofriyaldi, Ali (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2025)
There are many major problems with the skin, especially the face, that occur in some men and women. Acne is a skin disorder characterized by inflammation of the skin. Acne caused by Propionibacterium acnes bacteria is generally treated by Clindamycin capsules 300 g. However, the drug clyndamicin used by the oral route has side effects. So, there are alternative anti-acne drugs that have fewer side effects. Clove leaves from the clove tree can be used as medicine. The tannin compounds in clove leaves have antibacterial activity. In this research method, an acne patch preparation is made from clove leaf extract (includes collecting the ingredients to be tested, namely clove leaves, processing simplicia, making extracts, making acne patch formulations, and testing the antibacterial activity of Propionibacterium acnes using the well method. The results of the highest inhibition large, namely at F3 (10%) at 21,213mm very strong, F2 (7.5%) at 19,658mm strong and F1 (5%) at 18,788mm strong.